Assessment of prognostic performance of Albumin–Bilirubin, Child–Pugh, and Model for End-stage Liver Disease scores in patients with liver cirrhosis complicated with acute upper gastrointestinal bleeding. Issue 6 (June 2018) - Xavier, Sofia A.; Vilas-Boas, Ricardo; Boal Carvalho, Pedro; Magalhães, Joana T.; Marinho, Carla M.; Cotter, José B.
Abstract : Objective: The Albumin–Bilirubin (ALBI) score was developed recently to assess the severity of liver dysfunction. We aimed to assess its prognostic performance in patients with liver cirrhosis complicated with upper gastrointestinal bleeding (UGIB) while comparing it with Child–Pugh (CP) and Model for End-stage Liver Disease (MELD) scores. Patients and methods: This was a retrospective unicentric study, including consecutive adult patients with cirrhosis admitted for UGIB between January 2011 and November 2015. Clinical, analytical, and endoscopic variables were assessed and ALBI, CP, and MELD scores at admission were calculated. Results: This study included 111 patients. During the first 30 days of follow-up, 12 (10.8%) patients died, and during the first year of follow-up, another 10 patients died (first-year mortality of 19.8%). On comparing the three scores, for in-stay and 30-day mortality, only the ALBI score showed statistically significant results, with an area under the curve (AUC) of 0.80 ( P <0.01) for both outcomes. For first-year mortality, AUC for ALBI, CP, and MELD scores were 0.71 ( P <0.01), 0.64 ( P <0.05), and 0.66 ( P =0.02), respectively, whereas for global mortality, AUC were 0.75 ( P <0.01), 0.72 ( P <0.01), and 0.72 ( P <0.01), respectively. On comparing the AUC of the three scores, no significant differences were found in first-year mortality and global mortality. Conclusion: In our series, the ALBI score accurately predicted both in-stay and 30-day mortality, whereas CP and MELD scores could not predict these outcomes. All scores showed a fair prognostic prediction performance for first-year and global mortality. These results suggest that the ALBI score is particularly useful in the assessment of short-term outcomes, with a better performance than the most commonly used scores.